Strategi Pembelajaran Heuristik dalam Meningkatkan Kemampuan Menyelesaikan Soal Cerita Pada Materi Teorema Pythagoras Siswa Kelas VIII C SMP Unggulan Al-Yasini Pasuruan - Fatmah Daniyah Hanum (Fraktal : Jurnal Matematika dan Pendidikan Matematika, 2022)
This study aims to describe the ability of students to solve story problems on the Pythagorean theorem material using structured and systematic stages, namely by doing heuristic learning strategies. The method used is Classroom Action Research (CAR) which is carried out in collaboration with teachers. The CAR design used is the Kemmis and Mc model. Taggart which consists of planning, action, observation and reflection activities. CAR was carried out on class VIII C SMP Superior Al-Yasini Pasuruan. The data analysis technique was carried out descriptively by looking at the percentage of student learning outcomes. In the first cycle, a description of the students' abilities was obtained, but this did not meet the predetermined classical completeness. So that the implementation of the action is carried out based on the reflection of cycle 1. In the second cycle there is a significant increase. Learning outcomes in cycle 1 obtained an average of 78.75, then increased in cycle 2 with an average of 85.67 so that the significant difference between the two cycles is 14.3%. Thus, it can be concluded that the action applied is declared successful and can improve students' ability to solve story problems. Keywords: Heuristic Learning Strategy, Pythagorean Theorem Material, Story Problems